"UN FILM EXPERIMENTAL: BATTERIES DOGON, ELEMENTS POUR UNE ETUDE DE RYTHMES”, L'HOMME. Gilbert Rouget. Revue Francaise d'Anthropologie, V-2, 1965. - Kubik, Gerhard (International Library of African Music, 1969)
pages: 104
Keywords: African Music